2011
DOI: 10.1177/1476718x10366729
|View full text |Cite
|
Sign up to set email alerts
|

Emerald dragon bites vs veggie beans: Fun food names increase children’s consumption of novel healthy foods

Abstract: Caregivers often struggle with food neophobia on the part of young children. This study examined whether labeling novel healthy foods with fun names would increase children's willingness to try those foods and encourage them to eat more of those foods in a child care setting. Thirty-nine toddler and preschool age children (mean age = 3.9 years) were served each of three foods twice, once labeled with a fun name and once with a healthy name. Percentage of the food consumed by each child was recorded. Overall, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The nursery had recently introduced some changes to the menus to improve the nutritional value of the food and new dishes included food that the children were not necessarily familiar with and may be reluctant to try. Food neophobia, a fear of eating unfamiliar food, is a source of difficulty for caregivers of young children (Musher‐Eizenman et al., 2011). The practitioners were keen to find out if the children were eating the food provided, which they did through observations of the children's eating pattern throughout the day.…”
Section: Resultsmentioning
confidence: 99%
“…The nursery had recently introduced some changes to the menus to improve the nutritional value of the food and new dishes included food that the children were not necessarily familiar with and may be reluctant to try. Food neophobia, a fear of eating unfamiliar food, is a source of difficulty for caregivers of young children (Musher‐Eizenman et al., 2011). The practitioners were keen to find out if the children were eating the food provided, which they did through observations of the children's eating pattern throughout the day.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, exposing adults to information suggesting that limiting junk food consumption can be beneficial to health, reduced junk food consumption relative to a control condition in a recent study ( Robinson, Harris, et al., 2013 ). However, there are also studies which suggest that, in some contexts, health messages may not be an effective way to increase fruit and vegetable intake ( Maimaran and Fishbach, 2014 , Musher-Eizenman et al., 2011 , Wardle and Huon, 2000 ). For example, Maimaran and Fishbach (2014) showed that presenting food as instrumental to achieving a goal, for example, outlining the health benefits of eating certain foods, decreased consumption in pre-school children.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that tactics similar to those used to sell deceptively unhealthy foods could be utilized to sell actually healthy foods. For example, Musher-Eizenman et al (2011) increased toddler and preschoolers' consumption of vegetables by giving them fun names (e.g. edamame was named Emerald Dragon Bites).…”
Section: Suggestions For Future Directionsmentioning
confidence: 99%